Implementation Of Decisions And Obstacles Administrative Court - Implementation Obstacles - Hasto Sasmito (Jurnal Daulat Hukum, 2018)
Indonesia is a country of law. The rule of law means in our country is the law that has significance especially in all aspects of community life. Everything implementation carried out by the state through its government should be appropriate and according to the channels that have been determined in advance by law. Judicial Administration is a special court, which was given the authority to resolve disputes that arise in the field of administration and personnel or disputes that occur between administration officials with a person or body of civil law as a result of the issuance or issuance of a decision. Act no. 5 of 1986 on State Administration aims to provide a container or a space for people and civil legal entity to file a lawsuit to the Administrative Court (PTUN) for the issuance of an administrative decision (KTUN), then his rights to feel disturbed or harmed but in practice administrative court ruling will not necessarily be implemented because of constraints exist that impede the implementation of the decision of the Administrative Court. Thus the presence of the administrative court as an institution that is expected to be a means of enforcement and legal protection in the field of administration can not be carried out effectively and still needed revision of the law.Keywords: State Administrative Court (PTUN).